2017
DOI: 10.1016/j.compositesa.2016.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Stress ratio dependence of fibre bridging significance in mode I fatigue delamination growth of composite laminates

Abstract: This paper aims to investigate stress ratio effect on fibre bridging significance in mode I fatigue delamination growth of composite materials. Fatigue resistance curves (R-curves) of different stress ratios are determined and compared with the quasi-static R-curve. The fatigue R-curve of a high stress ratio is similar to the quasi-static results. However, fatigue resistance of a low stress ratio is smaller than quasi-static resistance. These indicate that fibre bridging significance is stress ratio dependent.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 29 publications
(56 reference statements)
0
31
0
Order By: Relevance
“…The results also demonstrated that fibre bridging can decrease fatigue crack growth. Yao et al [14][15][16] experimentally examined FDG with different amounts of fibre bridging and proposed empirical power law relations to determine fibre-bridged FDG behaviors. Furthermore, it was reported that the significance of fibre bridging was related to loading regime.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results also demonstrated that fibre bridging can decrease fatigue crack growth. Yao et al [14][15][16] experimentally examined FDG with different amounts of fibre bridging and proposed empirical power law relations to determine fibre-bridged FDG behaviors. Furthermore, it was reported that the significance of fibre bridging was related to loading regime.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, one can reason that the resistance curve (R-curve) obtained in quasi-static delamination cannot well represent resistance increase in fatigue delamination. In addition, it has been proven that stress ratio also affected the significance of fibre bridging, due to crack closure or other unknown reasons [16,18]. Particularly, fibre bridging of a high stress ratio delamination was much more significant than that of a low stress ratio.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obvious differences in the amount of fibre bridging in quasi-static and fatigue delamination were also observed in an experimental study conducted by Yao et al [20]. Furthermore, it was recently reported that the significance of fibre bridging in fatigue delamination was dependent on stress ratio [27]. More fibre bridging can be present in a higher stress ratio fatigue delamination.…”
Section: Introductionmentioning
confidence: 66%
“…(1). According to previous studies [20,27], the use of this relation was an effective way to qualitatively evaluate the significance of fibre bridging in fatigue delamination in composite laminates.…”
Section: Fatigue Delamination Modelsmentioning
confidence: 99%